Payments for ecological restoration and internal migration in China: The sloping land conversion program in Ningxia - Sylvie Démurger; Haiyuan Wan (IZA Journal of Migration, 2012)
This paper analyzes the impact of the Sloping Land Conversion Program (SLCP) on rural labor migration in China. We use recent survey data from Ningxia Hui Autonomous Region and a difference-in-difference approach to assess the impact of the policy on labor migration decision. We find a significant effect of the policy: the migration probability increase due to the SLCP policy amounts to 17.5 percentage points in 2008. Furthermore, we highlight the role of policy duration in strengthening the impact of the program on migration. We also find that young, male and Hui nationality individuals are more likely to be impacted by the policy.
Keywords: J22; J68; O13; Q23; 330; sloping land conversion program; labor migration; policy evaluation; China